Enhancing Knowledge Creation in Organizations - Ng Sin, Pei (2008)
The objectives of this study are to understand the importance of knowledge creation in organizations and to explore the ways to enhance knowledge creation in organizations. Knowledge creation is important in the sense that innovation is driven by the creation of knowledge and knowledge creation is perceived us one of major assets. This paper identifies and explores three ways to enhance knowledge creation, namely via 1.) using the right KM strategy to support business strategy, 2.) practicing the relevant leadership behaviours, and 3.) cultivating organizational learning culture.